2021
DOI: 10.47626/2237-6089-2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers in treatment-responsive and treatment-resistant schizophrenia patients

Abstract: Introduction: Schizophrenia is a complex psychiatric disorder that affects approximately twenty million people worldwide. Various factors have been associated with the physiopathology of this disease such as oxidative stress, which is an imbalance between pro-oxidant and antioxidant molecules. Objective: This study evaluated the association between biomarkers of oxidative stress and response to pharmacological treatment among patients with schizophrenia in the context of their clinical information, demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The fact that the patients are male, smokers, and have a disease duration of less than five years indicates differences in caspase-3 gene expression. Smoking that is related with oxidative stress in schizophrenia patients [37] may be an independent factor to induce caspase activation. Yu et al [38] showed that smoking increased cell apoptosis, causing an elevated cleaved-caspase 3/pro-caspase 3 ratio, and Bax expressesion but decreased Bcl-2 signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the patients are male, smokers, and have a disease duration of less than five years indicates differences in caspase-3 gene expression. Smoking that is related with oxidative stress in schizophrenia patients [37] may be an independent factor to induce caspase activation. Yu et al [38] showed that smoking increased cell apoptosis, causing an elevated cleaved-caspase 3/pro-caspase 3 ratio, and Bax expressesion but decreased Bcl-2 signals.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the patients are male, smokers, and have a disease duration of less than five years indicates differences in caspase-3 gene expression. Smoking that is related with oxidative stress in schizophrenia patients [ 37 ] may be an independent factor to induce caspase activation. Yu et al .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 GSTM1 null genotype might increase risk of SZ through brain inflammation induced by enzyme inactivity. [35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…GST genes were widely present in human body and were abundant in the kidney, liver, and lung. [36][37][38] In addition, GSTM1 and GSTP1 were detected in both human and rodent brains. 39 Notably, GSTM1 was also suggested that it is one of the most abundant proteins in astrocytes.…”
mentioning
confidence: 99%
“…Its annual prevalence was as high as 0.6% ( 1 ), which has a far-reaching impact on personal life and society, and it is easy to lead to lifelong disability. At present, the treatment of SCZ is still mainly drug treatment, its curative effect is limited, and adverse drug reactions are difficult to avoid, although it does not make the antipsychotics not being tolerable in most cases ( 2 ). Additionally, it has been suggested that identifying different discontinuation patterns for antipsychotics may contribute to optimize treatment selection in SCZ ( 3 ).…”
Section: Introductionmentioning
confidence: 99%